TINJAUAN HUKUM TERHADAP HIBAH TANAH YANG DISENGKETAKAN OLEH AHLI WARIS PARA PIHAK (STUDI : HIBAH TANAH ANTARA MIAK ASIN IMAM MULIA DAN SYARKAWI DT MAJO LELO DI NAGARI SITANANG) - Maulana Ihsan Habibi; Evi Deliana; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Customary law grants are divided into two, namely ordinary grants and will grants. Grants according to Minangkabau customary law are closely related to Islamic law. The implementation of the Grant refers to the Matrilineal system, which means a hereditary system based on the mother's lineage. In addition, the transfer of land rights through community grants and inheritance can also be given to heirs who are one descendant of the mother but can also be given to the lateral line, namely between mamak and nephews. In the field practice, especially in the Kenagarian area of Sitanang, Agam Minangkabau, there was a problem of disputes between the heirs of the two parties, the grantee and the grantee. the object in dispute is the land grant of the people which is the high inheritance of the Caniago clan.This research is to determine the extent of the implementation of the disputed land grant by the heirs of the parties in Nagari Sitanang according to Minangkabau customary law. This type of research can be classified in the type of sociological legal research (empirical), because in this study the author directly conducted research at the location or place being studied in order to provide a complete and clear picture of the problem under study. This research was conducted in the Nagari Sitanang area, Ampek Nagari District, Agam Regency, due to the location of the Adat Nagari Sitanang Institute, while the population and samples were Mamak Kepala Waris, Kerapatan Adat Nagari Sitanang, Wali Nagari Sitanang, and disputing inheritor. The data sources used are primary data and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusions that can be obtained from the results of the research are First, that in the Minangkabau Customary Law, the validity of a land that has been granted is that it has the approval of all members of the clan and meets the conditions for giving a clan grant.Keywords: Existence - Land Grants for the People - Indigenous Community of Nagari Sitanang